2003
DOI: 10.1034/j.1399-3089.2003.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine cytomegalovirus in pigs being bred for xenograft organs: progress towards control

Abstract: In human medicine, human cytomegalovirus (HCMV) is readily transmitted by organ transplant causing end-organ disease and triggering graft rejection in recipients. Because of a chronic shortage of human organs, pigs transgenic for human complement control proteins are being considered as potential donors. Such xenotransplantation raises concerns about the potential zoonotic transmission of viruses including porcine cytomegalovirus (PCMV), an endemic infection of pigs. Similar to HCMV and PCMV transmission is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 29 publications
5
66
0
Order By: Relevance
“…However, it is important to note that previous pig-to-human xenotransplantations have failed to reveal even a single instance of PERV transmission to a human subject (43). Moreover, a recent study has suggested that PERV could be eradicated from pig herds bred for xenotransplantation (44). Thus, as suggested recently by Ogata and Platt (45), although the potential danger of PERV to public health cannot be entirely dismissed, it should be approached with careful attention to the xenograft recipients, rather than necessitating that xenotransplantation studies be abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that previous pig-to-human xenotransplantations have failed to reveal even a single instance of PERV transmission to a human subject (43). Moreover, a recent study has suggested that PERV could be eradicated from pig herds bred for xenotransplantation (44). Thus, as suggested recently by Ogata and Platt (45), although the potential danger of PERV to public health cannot be entirely dismissed, it should be approached with careful attention to the xenograft recipients, rather than necessitating that xenotransplantation studies be abandoned.…”
Section: Discussionmentioning
confidence: 99%
“…However, the theoretical risk of a zoonotic, cross-species transmission of an infectious pathogen remains a concern (27,36). Whereas exogenous pathogens can be removed by specific-pathogen-free breeding, these techniques cannot exclude inherited agents such as endogenous retroviruses that are passed down via the germ line (6,34,35).…”
mentioning
confidence: 99%
“…Xenotransplantation carries the concerns of cross-species transmission of infectious pathogens present in the donor species (7,17,18,23). Studies indicate that many exogenous microorganisms can be eliminated from the donor herd by using various barrier methods and specialized qualified-pathogenfree rearing techniques (3,25,26). However, porcine endogenous retroviruses (PERVs) are an exception to this rule, as proviral copies are inherited through the germ line DNA.…”
mentioning
confidence: 99%